2008
DOI: 10.1007/s00595-007-3657-7
|View full text |Cite
|
Sign up to set email alerts
|

Current progress in neonatal surgery

Abstract: Neonatal surgery is the most specialized and sophisticated field of pediatric surgery. I herein review esophageal atresia, abdominal wall defects, gastrointestinal perforation, and congenital diaphragmatic hernia (CDH) as representative types of neonatal surgery. The clinical results of esophageal atresia have been considered to reflect the level of medicine of an individual country. Owing to an early diagnosis, improved operative techniques, and better perioperative management, the mortality rate has now beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 40 publications
1
14
0
2
Order By: Relevance
“…This overall mortality, relating to a surgical PICU population of risk, is within the prevalence reported for developed countries, which is usually below 10% 13 . To place results in context, nowadays, global neonatal surgical mortality is variable, especially depending on the level of development of the country.…”
Section: Discussionmentioning
confidence: 58%
“…This overall mortality, relating to a surgical PICU population of risk, is within the prevalence reported for developed countries, which is usually below 10% 13 . To place results in context, nowadays, global neonatal surgical mortality is variable, especially depending on the level of development of the country.…”
Section: Discussionmentioning
confidence: 58%
“…Apart from the delayed presentation as in our study, we can attribute this high figure to the overcrowded nature and poor ventilation of the special care baby room (resuscitaire). On the other hand, the study done in Intensive Care Unit of the Coimbra's Pediatric Hospital Portugal; Europe by Catré et al (2014) (7) found that there was an overall mortality of 6.4% and according to (Taguchi, 2008) (12) this mortality relating to a surgical NICU population of risk, is within the prevalence reported for developed countries, which is usually below 10% the most common cause of death in Portugal is Peritonitis/Abdominal sepsis 42% while sepsis represented 7%. In the current study, (18.84%) of neonates had positive blood cultures while (81.16%) had no growth and the most common organism was Klebsiella 46% then Acetobacter 23% then E coli 7%, and non-hemolytic streptococci 7%, Pseudomonas 7% and Staphylococcus aureus (coagulase negative ) 7%.…”
Section: Methodsmentioning
confidence: 99%
“…The mortality rate has become less than 10% [1]. It is now important to consider the long-term good ''quality of life'' (QOL) in neonatal surgical disease.…”
Section: Introductionmentioning
confidence: 99%